An online badminton motion tracking system - Abdul Aziz, Normaziah; Odenan, M. Amar; M. Khadafi, Taufiq (IIUM Press, 2011)
This chapter presents a sport scene tracking system for badminton using video input where a single player's performance can be analyzed. A player's performance is being tracked in terms of distance, speed and acceleration during a specific event. A color filtering method is applied to filter the video and differentiate between moving and non moving objects. The coordinates from the first frame till the last frame are tracked and applied to get the distance coverage, speed and acceleration of the player. Analysis and comparison of videos between two world champion badminton players were made as a test case. Overall, this study provides a proof of concept that movement of player can be tracked by computer vision and it is even better than analyzing it manually by human eyes